Transcendence techniques and psychobiological mechanisms underlying religious experience - Bartocci, Goffredo (Mental health, religion & culture, 2004)
In this paper the author explores the process by which the combined influence of specific cultural factors and individual transcendence techniques activates psychobiological mechanisms that, in turn, trigger the appearance of special states of consciousness, namely religious trance. Most of these religious and spiritual experiences rationalize a threat common to all cultures, namely the risk of losing one's Ego. The activation of individual transcendence techniques paraphrases denial defence mechanisms insofar as it involves avoidance of the external reality to preserve homeostasis. The mentioning in psychoanalytic terms of a ‘death instinct’ (i.e. a drive opposite to the attachment/life instinct) as a possible source of detachment/transcendence phenomena is still worth considering. The Freudian example of ‘the cotton-reel mother’, whom the child could make disappear and then reappear again, is a powerful one of the phenomenon of detachment dynamics. Cross-cultural research on the varieties of trance shows that Altered States of Consciousness can be induced by both collective and personal rituals that allow the subject to reach the altered states of consciousness by making the whole world appear or disappear in fantasy. While some of the highest forms of supernatural experience, such as ecstasy, mysticism and the communion with the Absolute, engender enough social approval to allow to believe that such experiences mitigate or prevent mental disorders, when the supernatural experiences occur in bizarre features they are indicators of a clear psychopathology. The perspective of transcultural psychiatry offers the best method of outlining the great ethnographic variety of these experiences and, subsequently, making a comparative analysis of the links that exists among culture, psychopathology and the supernatural in a given situation. From a clinical point of view, it becomes increasingly clear that psychiatrists need expertise to draw clinical inferences based on the specific patient's culture and his psychopathological presentation, especially when the patient's life history is characterized by the multi-faceted activity of transcendence techniques.